Anyone : the cosmopolitan subject of anthropology - Rapport, Nigel, 1956- (Methodology and history in anthropology, 2012)
The significance that people grant to their affiliations as members of nations, religions, classes, races, ethnicities and genders is evidence of the vital need for a cosmopolitan project that originates in the figure of Anyone & amp;ndash; the universal and yet individual human being. Cosmopolitanism offers an alternative to multiculturalism, a different vision of identity, belonging, solidarity and justice, that avoids the seemingly intractable character of identity politics: it identifies samenesses of the human condition that underlie the surface differences of history, culture and society, nat.